THE PERSUASION TECHNIQUES OF RHETORIC AT GEORGE WALKER BUSH ADDRESSES - Sufidiana, Risda; Wiyanto, M. Saibani (Prosiding Conference on Research and Community Services, 2019)
Rhetoric is an art of persuasion. In a speech, persuading listeners or audience is really needed in order to go to the ideas of the speaker. George Walker Bush has a big role to persuade the audience. Rhetoric refers to three persuasion techniques. This research is aimed to know the persuasion techniques are used and delivered by George Walker Bush Addresses to the utterances. The result of this research is expected to give contribution to the university students of addresses in speaking and writing form. In presenting the data, this research conducted by using descriptive qualitative research and using documentation method. Here, the words are analyzed descriptively to describe and explain in detail the phenomenon of words based on the rhetoric study. The source of data is taken from americanrethoric.com and the data is the script of George W. Bush addresses that is taken from lastest addresses on that site. The result of the research shows that at George W. Bush addresses, there are three kinds of persuasion techniques that he used in every speech, those are logos, ethos, and pathos. Pathos is the most dominant rhetoric from those three addresses.